A Multisensor Analysis of the Life Cycle of Bow Echo over Indian Region. (29th October 2014) - Dutta, Devajyoti; Sarma, Diganta Kumar; Sharma, Sanjay
Abstract : This study deals with the life cycle of bow echo events on October 24 and 26-27, 2006, from Doppler weather radar (DWR) observations supported by Radiosonde and National Centers for Environmental Prediction (NCEP). The cell bow echo (CBE) on October 24 evolved from two small isolated cells with radar reflectivity ≥40 dBZ. The vertical structure consists of one single mature cell with 20 dBZ echoes reaching up to 10 km while 40 dBZ echoes extended uniformly from ground to ∼5 km height. The radial velocity shows a high value >−15 m/s towards the radar at the upper height (about 6 to 11 km); the lower height is predominant with velocity away from the radar (about 5 to 15 m/s). The squall line bow echo on October 26 and 27 has its origin over ocean and moved towards the radar site and decayed thereafter. The radar reflectivity pattern for this squall line showed it to be a trailing stratiform type squall line with length of ∼200 km. The echo top height was more than 12 km in height. Strong inflow cases were observed from both radiosonde and radar.